Effect of hot pressing densification on the cellular structure of black agglomerated cork board (European Journal of Wood and Wood Products, 1994)
Samples of black cork agglomerate boards were observed by scanning electron microscopy, prior and after different densifi- cations. These boards were densified under conditions previous- ly defined, and were observed in two directions, parallel and per- pendicular to the compression axis. The relationship between the average cell wall distance and the compression applied was stud- ied and it was found that the maximum densification is achieved with a pressure of ca. 3 MPa. Some aspects of the influence of densification treatments on the chemical composition of the material were also broached.